Catalytic Ketone Hydrodeoxygenation Mediated by Highly Electrophilic Phosphonium Cations1. Issue 28 (1st June 2015) - Mehta, Meera; Holthausen, Michael H.; Mallov, Ian; Pérez, Manuel; Qu, Zheng‐Wang; Grimme, Stefan; Stephan, Douglas W.
Abstract Ketones are efficiently deoxygenated in the presence of silane using highly electrophilic phosphonium cation (EPC) salts as catalysts, thus affording the corresponding alkane and siloxane. The influence of distinct substitution patterns on the catalytic effectiveness of several EPCs was evaluated. The deoxygenation mechanism was probed by DFT methods.